Breaking barriers a study on the implementation, sustainability and user/community perception of a "free library" based on the Reading Club 2000 in Barangay La Paz, Makati City - Imperial, Chris Martin T.; Santos, Yhna Therese P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Since its inception in the year 2000, the Reading Club 2000 in Brgy. La Paz, Makati City has gained popularity among local and international media because of its "free library" system. The library has a revolutionary system that allowed its users to access the collection for free. Its books were given away for free in a library that never closes. The system exuded a huge potential to augment the coverage of public libraries in the Philippines. It is in this light that this study has coined the term, investigated library's sustainability and focused on the Reading Club 2000 being a template for all similar libraries that would follow.
Mr. Hernando Guanlao, the man behind the library, was interviewed to uncover the methods he employed in the library that made it exist for a long time. A sample of 37 users and residents of the barangay were also interviewed to determine their perceptions on the different aspects of the library. A SWOT Analysis was also accomplished in support of the data gathered.
The information gathered revealed that: (a) 21 out of 37 (56.76%) respondents were women and 17 out all the respondents were aged 40 and above (45.95%); (b) 27 (72.97%) of the respondents have been in the library and 26 of these do so regularly to frequently; (c) most of the respondents have borrowed, claimed and donated a book at least once; (d) all of the respondents had a positive perception on the effect of the Reading Club 2000 on their level of education; and (e) all of the respondents believe that having a free library in another community would have a positive effect on its residents.
The information gathered revealed that: (a) 21 out of 37 (56.76%) respondents were women and 17 out all the respondents were aged 40 and above (45.95%); (b) 27 (72.97%) of the respondents have been in the library and 26 of these do so regularly to frequently; (c) most of the respondents have borrowed, claimed and donated a book at least once; (d) all of the respondents had a positive perception on the effect of the Reading Club 2000 on their level of education; and (e) all of the respondents believe that having a free library in another community would have a positive effect on its residents.
The interview with Mr. Guanlao revealed the library's dependence on donations and marketing. Many donors were rich and most of them were returning donors who have done marketing for Guanlao. Social networking sites were also used as a marketing tool.
Observations and findings done in the Reading Club 2000 were applied to free libraries in general. It was found out that: (a) sustainability is highly dependent on the willingness of the community to help; and (b) sustainability is also dependent on the commitment of the owner and his/her ability to create and maintain an impressive network of donors.
Recommendations include: (a) formulating an informal collection development policy and vision and mission; (b) improving the sorting and storage of books; (c) developing a better program for educational services; (d) improving marketing strategies; (e) Cleaning and performing aesthetic improvement of both interior and exteriors; and (f) beefing up of security.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Reading Club 2000.; Public libraries -- Philippines -- Makati City -- Use studies; Library Clubs -- Philippines -- Makati City